First trials with naked winter oats varieties - Antonova, Nadezhda (MTT, 2004)
Bulgaria is in a zone of marked transition-to-continental climate. Oat cultivation under these conditions is limited by temperature and rainfall. The data over 100 years show that the drought periods in spring and spring-summer are on increase (Cholakov 2003), which makes winter-crop realization more certain. However, temperature conditions in the autumn-winter period can totally compromise a crop, thus disheartening the producers. The average cold-resistance coefficient for the naked varieties of winter oat was found to be ê=2, 3 at k=11 for barley, var. Mirage (Antonova & Petrova 2002). Winter oat has to have a coefficient of 10 to guarantee its survival. The aim of the research is estimating the basic agronomic parameters of naked oat varieties and lines in order to formulate a selection strategy. Eighteen naked oats varieties and lines after two preliminary frost tests at -10 12 oC were evaluated 2000 - 2003 in a randomized block design. We measured cold resistance using coefficient of cold resistance (Antonova & Petrova 2002), resistance to Puccina gr. and P. coronata, f. avenae, yield with its components and seeds characteris. Years were characterized by meteorological parameters. Stable and high yielding code were 48 and Bullion. Promising genotypes as parents in a cross combinations are: Bandicoot and Carma for radically earlier vegetative period, Bandicoot for very short plant height; Cn 91/257/4 for high 1000 grain mass; Neon and ÊÇ- 32-78 protein and lysine content. Fats were <7% for all genotypes. There were no outstandingly promising samples as to the degree of nakedness and the discolouration is not a problem for Bulgarian conditions. The genotypes from the UK had high yield potential, medium plant height, lodging resistance but not sufficient cold resistance. As a contribution to the breeding process were established very significant positive phenotypic correlations between yield, main panicle grain weight and test weight (Pixlej & Frey 1992). The weight of the grains in the main panicle is determined by the weight of the main panicle and the rate of grain growth (Peltonen-Sainio 1990). The main selection aim remains wintertolerance combined with high productivity, which requires a broadening of the naked winter oat genetic stock, including the use of spring varieties. Antonova & Petrova, 2002. Jubilee Session on the 50th Anniversary of the Dobroudja Agricultural Institute Breeding and Agrotechnics of Field Crops; 191-198; Cholakov 2003. Scientific Session of Jubilee 120 Years Agriculture Science in Sadovo. Scientific Reports. Vol. III; 154 158; Peltonen-Sainio, P. 1990. Plant Breeding 104: 340-354; Pixlej & Frey, K.J. 1992. Euphytica 60: 149-156.
Keywords: Ka; naked oats; grain yield; cold tolerance; quality